Structure of Ag-Cu clusters resolved by absorption, Raman and vibrational spectroscopy. Issue 1 (August 2021) - Li, Weiyin; Zhao, Tongtong; Ding, Lingling; Zhang, Sha
Abstract: The structures of Ag9, Ag10, Ag8Cu1, and Ag6Cu3 clusters and their optical, Raman and vibrational spectra are calculated by GGA/PBE. The results display that the structures of the Ag9, Ag10 and Ag8Cu1 (three isomers) clusters can be distinguished by comparing their energies and optical, Raman and vibrational spectra. The difference between the two isomers of the Ag6Cu3 clusters cannot be distinguished by comparing their energies and cannot be directly observed, with their uniform shapes proved by their optical, Raman and vibrational spectra.